(untitled) (International Journal of Built Environment and Sustainability, 2020)
Recently, Shopping malls are introduced in Algerian cities as new commercial structures instead of traditional markets; they become a part of the daily life allowing people to have a new shopping experience. This paper aims to explore the influence of visual accessibility and spatial configuration on the navigation of individuals in a shopping mall through the analysis of Bab-Ezzouar shopping centre. The analysis of spatial and visual patterns adopts space syntax techniques and methods, a survey analysis based on people tracking and a questionnaire is applied to collect data on the shopping centre visitors’ behaviour. The results show that the perception of shopping spaces differs from familiar to unfamiliar visitors, familiar visitors are guided by their shopping habit more than spatial patterns and unfamiliar visitors are influenced by visual patterns of space more than accessibility. Visitors tend to choose the most open spaces that offer maximum visual accessibility more than physical accessibility, they also prefer walking in a straight-line avoiding change of direction. These features can guide designers in their process for better understanding of shopping space.